The implementation of rifapentine and isoniazid (3HP) in two remote Arctic communities with a predominantly Inuit population, the Taima TB 3HP study. Issue 1 (1st January 2020) - Alvarez, G. G.; Van Dyk, D.; Mallick, R.; Lesperance, S.; Demaio, P.; Finn, S.; Potvin, S. Edmunds; Patterson, M.; Pease, C.; Amaratunga, K.; Hui, C.; Cameron, D.W.; et al.
ABSTRACT: Background : The incidence of TB among Inuit is the highest in Canada. A significantly shorter latent TB infection (LTBI) treatment with rifapentine and isoniazid once weekly for 12 weeks (3HP) is now available in limited settings in Canada. Methods : A prospective open﻿-label 2-year observational postmarketing study was conducted introducing 3HP for the first time in Canada in Iqaluit followed by a program rollout in Qikiqtarjuaq, Nunavut. Results : A total of 247 people were offered 3HP, 102 in the Iqaluit postmarketing study and 145 in the Qikiqtarjuaq program roll out. Although statistical significance was not reached, more people who started treatment completed treatment in the 3HP group (Iqaluit, 60/73 (82.2%) and Qikiqtarjuaq, 89/115 (77.4%)) than in the historical control 9INHgroup (306/420 = 72.9%) (p = 0.2). Most of the adverse events in 3HP treated patients were associated with mild discomfort but no disruption of normal daily activity. Not drinking alcohol was associated with increased 3HP completion (OR 13.33, 95% CI, 2.27–78.20) as was not taking concomitant medications (OR 7.19, 95% CI, 1.47–35.30). Conclusions : The present study supports the feasibility and safety profile of 3HP for the treatment of LTBI in Nunavut.